Design for the reduction of volume shrinkage-induced distortion in digital light processing 3D printing. (October 2021) - Zhang, Qiang; Weng, Shayuan; Hamel, Craig M.; Montgomery, S. Macrae; Wu, Jiangtao; Kuang, Xiao; Zhou, Kun; Qi, H. Jerry
Abstract: Due to its high printing resolution and fast printing speed, digital light processing (DLP) has become one of the most widely used additive manufacturing technologies. In a typical DLP printing, resin is photocured from liquid into solid accompanied by a large volume shrinkage, which often leads to shape distortion of printed structures. In this study, we investigated the volume shrinkage-induced distortion of DLP-printed parts by conducting experiments, theoretical modeling, and finite element analysis (FEA) simulations. Material property evolution coupled with volume shrinkage during photocuring was first modeled constitutively. The constitutive theory was then implemented into FEA simulations of the layer-by-layer DLP printing process to study the development of shape distortion due to volume shrinkage during printing. Experiments validated the efficiency of the proposed FEA simulations. FEA was further applied to help predict the shape distortion in printed microfluidic channels and overhanging structures where printing parameters for compensating for distortion can be designed based on FEA. Graphical abstract: